PENGARUH KOMITMEN PROFESIONAL, TEMPAT KENDALI INTERNAL, DAN KECERDASAN EMOSIONAL TERHADAP KEMAMPUAN MENDETEKSI KECURANGAN - Ryando Siahaan, Binur; Dewi Astuti, Tutut (JURNAL ILMIAH EDUNOMIKA, 2025)
Finding out how professional commitment, internal control, and emotional intelligence affect auditors' capacity to spot fraud in Public Accounting Firms (KAP) in the Special Region of Yogyakarta is the goal of this study. The study's backdrop is the poor quality of audits brought on by auditors' inaccuracies and ethical transgressions that undermine public confidence. 35 auditors chosen through purposive sampling were given a questionnaire as part of this study's quantitative survey methodology. SmartPLS 3.0 was used to evaluate the data using the SEM method. The findings from the hypothesis testing indicated that: "(1) Professional commitment has a positive and significant effect on the ability to detect fraud (t-statistic = 4.742); (2) Internal control environment has a positive and significant effect (t-statistic = 3.586); (3) Emotional intelligence also has a positive and significant effect (t-statistic = 2.366)" . According to this study, these three elements are essential for improving auditors' capacity to identify fraud.